ANALISIS DAMPAK IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) DAN SISTEM INFORMASI AKUNTANSI TERHADAP PENGENDALIAN INTERNAL - Teti Rahmawati; Yeni Yustian (Program Studi Akuntansi, Universitas Kuningan, 2022)
This study aimed to analyze the Impact of the Implementation of Enterprise Resource Planning (ERP) and Accounting Information Systems on Internal Control of Payrolls and Wages. The research method is descriptive and verificative. The research population is 109 employees who work at RSU El-Syifa Kuningan. The sampling technique used in this study is proportional purposive sampling. The data collection technique used a questionnaire technique while the data analysis technique used multiple regression analysis. The results of the study indicate that the Enterprise Resource Planning (ERP) system and the Accounting Information System simultaneously had a significant effect on the Internal Control of Payrolls and Wages. The Enterprise Resource Planning (ERP) system and the Accounting Information System partially have a positive and significant effect on the Internal Control of Payrolls and Wages.Keywords: Internal Control, Enterprise Resource Planning, Accounting Information System